2020
DOI: 10.3390/antiox9080717
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Tyrosine Hydroxylase Gene from Rat Leads to Oxidative Stress in Potato Plants

Abstract: Catecholamines are biogenic aromatic amines common among both animals and plants. In animals, they are synthesized via tyrosine hydroxylation, while both hydroxylation or decarboxylation of tyrosine are possible in plants, depending on the species, though no tyrosine hydroxylase—a counterpart of the animal enzyme—has been identified yet. It is known that in potato plants, it is the decarboxylation of tyrosine that leads to catecholamine production. In this paper, we present the effects of the induction of an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Potato plants contain many aromatics, where some exert noxious effects when accumulated to high concentrations within insect bodies (Gandia-Herrero and Garcia-Carmona, 2013 ; Kostyn et al, 2020 ). In this survey, we discovered that only 6 and 7 aromatics were accumulated in the larvae and adults, respectively, in contrast to 42 cumulated aromatics in the pupae ( Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Potato plants contain many aromatics, where some exert noxious effects when accumulated to high concentrations within insect bodies (Gandia-Herrero and Garcia-Carmona, 2013 ; Kostyn et al, 2020 ). In this survey, we discovered that only 6 and 7 aromatics were accumulated in the larvae and adults, respectively, in contrast to 42 cumulated aromatics in the pupae ( Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…These monoaromatics can be used to biosynthesize structurally complex substances. For instance, catecholamines, derived from tyrosine and phenylalanine, can be used to produce betalains, alkaloids, melanins, and hydroxycinnamic acid amides (Gandia-Herrero and Garcia-Carmona, 2013 ; Kostyn et al, 2020 ). To improve soil quality and increase crop yield, the plant residues, such as straws and stubbles after harvest, organic fertilizers, for example, manure and human excreta, and other organic landfills, are often applied to agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these studies suggest that increases in the catecholamine content of GM plants is likely a direct result of 14-3-3 protein mediated upregulation of endogenous tyrosine decarboxylase. is led to further analysis of the catecholamine biosynthesis pathway via several different approaches, including exogenous (from parsley) tyrosine decarboxylase or dopamine receptor (human) expression, which in turn revealed that these compounds are likely to serve the same biochemical functions in plant and humans, i.e., regulating glucose-starch balance and facilitating the stress response in potato plants (Kostyn et al, 2020;Skirycz et al, 2005;Świędrych et al, 2004).…”
Section: Engineered Potatomentioning
confidence: 99%